Banded Ferruginous hawk being held by D. Hanni - Unidentified photographer (Colorado State University. Libraries, 2005)
Banded FEHA held by D. Hanni, probably wider version of raptor begin held.
Keywords: birds; SGS; bird banding; raptor; Ferruginous hawk